Integrating Moderate Religious Values in Early Childhood Education: Analysis of Teachers' Roles and Strategies - Arie Dwi Ningsih; Veryawan Veryawan; Rabitah Hanum Hasibuan (Jurnal Raudhah, 2025)
Religious moderation is an important principle in maintaining harmony and tolerance in a multicultural society. Early childhood is a critical phase in character formation, so the values of moderation need to be instilled from an early age. This study aims to examine the role of teachers in instilling the value of religious moderation in early childhood through a literature review of 15 journals, both accredited and non-accredited. This study focuses on three main aspects, namely the concept of religious moderation, the principles of religious moderation in early childhood, and the role of teachers in its application. The results of the study show that teachers have a strategic role in instilling the value of religious moderation through thematic learning, an inclusive approach, and the creation of a learning environment that respects diversity.